ڕۆڵى جيهانگيرى لەسەر پرۆسەى پەروەردە وفێربوون توێژينەوەيەكى تيۆرى شيكارييە - محمد, پ.ى.د أحمد على حەمە; نورى, م. عادل محمد; يحي, م. سلام حسين (Sulaimani Journal for Humanities, 2023)
Globalization is closely related to the education and learning process, education has an important place in the expansion of globalization. The aim of this study is to explain and analyze the role of globalization on the education process. used the library Researchas it is theoretical research and tries to analyze the relationship between globalization and the education process. The results show that the Kurdistan Region has fallen under the influence of globalization thought, and globalization of education is an organized step and the purpose of these steps Building several unified and global educational systems and effort to reveal and sanctify a particular educational system, to inspire other nations to try to practice the same educational systems and incorporate them into their education systems, as well as tried to expose them through global education It sanctifies global values, so that the new generation has a tendency and love for this kind of global education and follow this method rather than follow the social and cultural values of their own society.
Keywords: (پەروەردە فێركردن جيهانگيرى پەروەردەى جيهانى)